2016
DOI: 10.1186/s12888-016-0759-z
|View full text |Cite
|
Sign up to set email alerts
|

The mental health status of ethnocultural minorities in Ontario and their mental health care

Abstract: Background: Mental disorders are a leading cause of disability and early mortality. The objective of this study was to describe and compare psychosocial indicators and mental health service use among ethnoculturallydiverse Ontarians. Methods: This is a cross-sectional analysis of the Ontario Health Study pilot investigation. Residents were mailed an invitation to one of 3 assessment centres (urban, rural and northern sites) from March 2009 to July 2010. Participants had an interview with a nurse and completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…These findings are not surprising because research has shown that being of non-White ethnic background is associated with more mental health problems. 62 With regards to distress, although K6 consistently showed very good reliability (as measured by Cronbach's alpha) when treated as a simple continuous scale, 4,23 our results showed that a twofactor model (representing anxiety and depressive symptoms) of the K6 had a better fit. These findings are consistent with previous studies indicating that a two-factor model representing anxiety and depression fit the data best in young adults 27 and older adults.…”
Section: Discussionmentioning
confidence: 70%
“…These findings are not surprising because research has shown that being of non-White ethnic background is associated with more mental health problems. 62 With regards to distress, although K6 consistently showed very good reliability (as measured by Cronbach's alpha) when treated as a simple continuous scale, 4,23 our results showed that a twofactor model (representing anxiety and depressive symptoms) of the K6 had a better fit. These findings are consistent with previous studies indicating that a two-factor model representing anxiety and depression fit the data best in young adults 27 and older adults.…”
Section: Discussionmentioning
confidence: 70%
“…Most studies focused on socio-demographical predisposing factors, encompassing ethnic minorities [6, 7], male gender [8], and those with low education level [9]. Cultural barriers, such as stigma [10], misconception of mental health problems [11], and mental health illiteracy [12] may also shape negative attitudes toward professional service.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there is evidence that First Nations people who represent ethnic minorities in their own country have poorer health relative to the mainstream population 5 . There is mounting evidence that First Nations people globally are affected by worse mental health relative to the mainstream population, including Aboriginal Canadians 6 7 , Maori in New Zealand 8 and Aboriginal and Torres Strait Islander (respectfully hereafter Indigenous) people in Australia, who are more than twice as likely to be hospitalised due to a mental disorder 9 . It is estimated that by closing the health gap in Australia, 5600 disability adjusted life years (DALYs) could be saved each year 10 .…”
mentioning
confidence: 99%